Who is Trading Well with China? A Gravity and Constant Market Share Analysis of Exports of Pakistan and ASEAN in the Chinese Market. (September 2022) - Abdul Kamal, Muhammad; Qayyum, Unbreen; Khan, Saleem; Ngozi Adeleye, Bosede
This paper empirically investigated the trade competitiveness and trade potential of Pakistan and ASEAN countries in the Chinese market. The study utilizes trade data for the period of 2003–2019 to assess the bilateral trade aspects by using an extended gravity equation. In addition, the PPML model and constant market share analysis are applied to examine trade potential and competitiveness, respectively. Market size, distance, trade openness, revealed comparative advantage position and common border play an important role in bilateral trade of Pakistan and ASEAN with China, and coefficients of all these variables comply with the economic theory and are statistically significant. Pakistan along with Brunei, Cambodia, Laos, Myanmar, Philippines, and Thailand has great trade potential in the Chinese market. Particularly Cambodia and Vietnam are enjoying the highest competitive advantage as compared to other ASEAN countries. Pakistan's export performance in China's market relies on the market distribution effect. Based on this study, we have discussed country-specific future policy discourse for Pakistan and ASEAN countries in detail.